La ville contre la diaspora : les Ottomans dans l’espace urbain de la monarchie des Habsbourg au xviiie siècle - David Do Paço (Diasporas: Circulations, Migrations, Histoire, 2016)
This article emphasises the different forms taken by the presence of the Ottoman merchants in the cities of the Habsburg Monarchy, at the time of a new commercial take-off following the Treaties of Karlowitz (1699) and Passarowitz (1718). A comparative analysis of the Ottoman urban spaces in Pest, Temesvár, Trieste and Vienna, follows a global assessment. Moving the focus away from the diasporas onto the city, this contribution explores the dynamics that led to the urban integration of foreigners, and doing so it provides an original social insight into the commensurability of the early modern Mediterranean and Central European cities, breaking with the identity agendas of the mainstream history of trading diasporas in the eighteenth-century Habsburg monarchy.